CHARACTERIZATION OF COCOA FUNCTIONAL DRINK PREPARATION FORTIFIED Chlorella vulgaris - Vattaah, Atiqah Nurul; Iriani, Dian; Sari, N. Ira (Asian Journal of Aquatic Sciences, 2024)
The cocoa drink is a beverage derived from processed cocoa beans. The antioxidant content of cocoa can be used as a basis for cocoa beverage development. One form of diversification of processed cocoa products is made drinks with Chlorella vulgaris fortification, which is rich in nutrients. This study aims to determine the effect of Chlorella vulgaris powder fortification on the quality characteristics of cocoa preparations and determine the best concentration for making cocoa drinks. The research method was experimental, using a factorial Completely Randomized Design (CRD) consisting of 4 different levels of formula concentration treatment, namely cocoa drink processing without Chlorella vulgaris powder fortification (KC0), 10% Chlorella vulgaris powder fortification (KC1), 15% Chlorella vulgaris powder fortification (KC2) and 20% Chlorella vulgaris powder fortification (KC3). The research parameters observed were characteristics of appearance, odor, flavor, and texture in hedonic testing, proximate composition (moisture, fat, protein, ash, carbohydrate content), solubility, antioxidant activity, and total phenolic testing. Based on the results showed that cocoa drink with 15% Chlorella vulgaris powder fortification (KC2) is the best concentration with organoleptic characteristics such as blackish brown cocoa drink, slightly fragrant chocolate odor typical of Chlorella vulgaris and cocoa, a slightly bitter taste, typical of Chlorella vulgaris and a slightly thick texture. The proximate composition is 3.18% moisture content, 11.10% fat, 7.95% protein, 3.86% ash and 73.92% carbohydrate. Meanwhile, the solubility is 67.69%, antioxidant activity is 177.92 mg/L, and phenolic content is 1.14 μg/mL. Therefore, this cocoa drink can be used as a functional drink